Exploring Exponential Functions Using Geogebra - Tuda, Shpresa; Rexhepi, Shpëtim (S&Co Publishing, 2023)
Exponential functions, symbolized by the expression f(x)=ax, are a fundamental mathematical concept widely applicable to real-world scenarios such as population growth, compound interest, and radioactive decay. This abstract underscores the significance of exponential functions and highlights GeoGebra's crucial role in interactive visualization and analysis as an intuitive mathematical software. This study utilizes GeoGebra's dynamic interface to explore and comprehend exponential functions, bridging the gap between theoretical concepts and practical applications. It includes a comparative analysis between classical methods and GeoGebra solutions for exponential functions. The software's ability to validate mathematical outcomes through visual confirmation is explored, emphasizing its role in not only enhancing understanding but also providing a reliable means of verification. GeoGebra and mathematical analysis illustrations consistently yield results through practical examples, demonstrating the software's effectiveness in fostering a deeper understanding of exponential growth. In addition, surveys was conducted and engaged in direct comparison of solutions with students in the classroom setting to observe firsthand how learners interact with the material and identify common mistakes made during problem-solving. The survey results informed the development and refinement of the approach, ensuring a comprehensive understanding of both the benefits and challenges associated with learning exponential functions through GeoGebra.